Synthesis of 3-alkenylindoles through regioselective C–H alkenylation of indoles by a ruthenium nanocatalyst - Paul, Abhijit (Beilstein J Org Chem, 2020)
3-Alkenylindoles are biologically and medicinally very important compounds, and their syntheses have received considerable attention. Herein, we report the synthesis of 3-alkenylindoles via a regioselective alkenylation of indoles, catalysed by a ruthenium nanocatalyst (RuNC). The reaction tolerates several electron-withdrawing and electron-donating groups on the indole moiety. Additionally, a “robustness screen” has also been employed to demonstrate the tolerance of several functional groups relevant to medicinal chemistry. With respect to the Ru nanocatalyst, it has been demonstrated that it is recoverable and recyclable up to four cycles. Also, the catalyst acts through a heterogeneous mechanism, which has been proven by various techniques, such as ICPMS and three-phase tests. The nature of the Ru nanocatalyst surface has also been thoroughly examined by various techniques, and it has been found that the oxides on the surface are responsible for the high catalytic efficiency of the Ru nanocatalyst.